Adaptive transmission schemes of cognitive radio for dynamic spectrum access using wavelets and multiwavelets - Manju Mathew (2012)
Electromagnetic spectrum is a natural resource and at present its use is regulated by fixed spectrum assignment policy. That is, spectrum is assigned to license holders or services on a long term basis for large geographical regions. This fixed channel allocation served well in the past but the rapid and tremendous growth in wireless communication changed the entire scenario. Introduction of every new communication application, either military or civilian makes the spectrum more and more congested. Meanwhile, the spectrum allocated to specific users does not ensure it is being used effectively at all times. Measurement studies reveal that 15 to 85 percent of the licensed radio spectrum is relatively unutilized or under utilized in most of the geographical locations for a considerable amount of time. The limited available spectrum and its inefficient usage encouraged a new communication paradigm to exploit the radio frequency spectrum opportunistically. This new concept is termed Dynamic Spectrum Access (DSA). The technology that makes DSA possible is Cognitive Radio (CR) which was first suggested by Joseph Mitola. In fact, CR is an all-encompassing term for a wide variety of technologies that enable radios to achieve various levels of self configuration and different functionalities ranging from ubiquitous wireless access to DSA for a device centric interference management. DSA networks define the already existing licensed users as primary users or legacy users and CR as secondary user. CR, sits on top of Software Defined Radio (SDR) is an intelligent wireless system that adapts to its environments to utilize the spectrum by its secondary usage in a 'do no harm' fashion. In simple words, it senses the radio environment, detects vacant spectrum bands, decides the best spectrum and chooses the transmission scheme which insures minimum interference to adjacent legacy users. As DSA networks targets mainly the wideband spectrum, the transmission technology should mitigate multi-path frequency selective fading channel impairments and should have multi-user support.